Sexual problems experienced by women in an HIV-1 crisis (Revista Latino-Americana de Enfermagem, 2000)
This descriptive study was based on the assumptions of qualitative investigation methods and on the Crisis Theory formulated by CAPLAN (1966). The objective of the study was to identify the sexual problems experienced by women undergoing an HIV-1 crisis. Data were collected through a semi-structured interview recorded by the method of FREITAS et al. (1992) and analyzed by the method of MEIHY (1996). Authors concluded that these women maintained themselves unbalanced using negative coping mechanisms. Thus, authors believe that it would be possible to help them using adequate nursing actions such as educational and guidance actions, but mainly by actions directed to the needs of patients undergoing an HIV-I crisis.